Comparative Carbon Footprint Assessment of commercial walk-in refrigeration systems under different use configurations - Cascini, A.; Gamberi, M.; Mora, C.; Rosano, Michele; Bortolini, M. (2016)
The design of refrigeration systems must strictly comply with the rules determined by the increasingly stringent international regulations on the use of refrigerants. Regardless of the restrictions imposed, the compliance with best practices in ecodesign may provide competitive leverage in the market, given its sustainability advantages. The replacement of fluorinated gases by latest generation hydrofluorocarbons (HFC)'s, or their complete ban, are considered necessary but not sufficient solutions for reducing the environmental damage caused by refrigeration systems: refrigerant retrofitting must include performance requisites, entail energy savings and generate a global environmental benefit. In this paper the environmental impact associated with the life cycle of two commercial refrigeration systems with walk-in cold rooms (for medium- and low temperature food storage) is investigated using a streamlined version of Life Cycle Assessment (LCA) methodology: Carbon Footprint Assessment (CFA). The environmental burden created by the refrigeration systems is evaluated by analysing the whole life cycle of the entity including the refrigeration unit and refrigerant. The environmental impact created by the adoption of alternative refrigerants (i.e. R-404A, R-407F, and R-410A) under different conditions (i.e. room set point temperature, refrigerant leakage rate) is also evaluated and discussed. CFA results are used as environmental performance indices in the final evaluation of the most sustainable configurations. The analysis of the whole refrigeration system life cycle demonstrates that the use-phase contributes significantly to the total environmental impact, and that indirect emissions resulting from refrigerating unit electric energy consumption are larger than those associated with refrigerant leakage. For the low-temperature (LT) system, the use of R-407F results in better environmental performance than R-404A and significantly minimises the overall system impact. Also for the medium-temperature (MT) system the retrofitting of R-404A introduces significant environmental advantages, but the optimal choice between R-410A and R-407F depends on the value of the operating set point temperature and leakage rate. Particularly given a set point temperature of 0 °C and a leakage rate of 10%, R-410A determines the best environmental performance. Instead with [10, 13]% of leakage rates and depending on the set point temperature, R-407F results the best solution.